CD44 deficiency inhibits unloading-induced cortical bone loss through downregulation of osteoclast activity - Li, Yuheng (Sci Rep, 2015)
The CD44 is cellular surface adhesion molecule that is involved in physiological processes such as hematopoiesis, lymphocyte homing and limb development. It plays an important role in a variety of cellular functions including adhesion, migration, invasion and survival. In bone tissue, CD44 is widely expressed in osteoblasts, osteoclasts and osteocytes. However, the mechanisms underlying its role in bone metabolism remain unclear. We found that CD44 expression was upregulated during osteoclastogenesis. CD44 deficiency in vitro significantly inhibited osteoclast activity and function by regulating the NF-κB/NFATc1-mediated pathway. In vivo, CD44 mRNA levels were significantly upregulated in osteoclasts isolated from the hindlimb of tail-suspended mice. CD44 deficiency can reduce osteoclast activity and counteract cortical bone loss in the hindlimb of unloaded mice. These results suggest that therapeutic inhibition of CD44 may protect from unloading induced bone loss by inhibiting osteoclast activity.